circRNA circFUT8 Upregulates Krüpple-like Factor 10 to Inhibit the Metastasis of Bladder Cancer via Sponging miR-570-3p - He, Qingqing (Mol Ther Oncolytics, 2020)
Circular RNAs (circRNAs) are broad and diverse endogenous non-coding RNAs. Emerging evidence has revealed that circRNAs play pivotal roles in cancers, regulating the gene expression by acting as a microRNA (miRNA) sponge. However, the biological functions of circRNAs in bladder cancer (BCa) remain largely unknown. In this study, we identified an altered circRNA, termed circFUT8, by screening RNA sequencing data generated from three BCa tissues and matched adjacent normal bladder tissues. Quantitative real-time PCR analysis demonstrated that circFUT8 was downregulated in BCa tissues and correlated with patients’ prognosis, histological grade, and lymph node (LN) metastasis. Functionally, gain- and loss-of-function assays indicated that circFUT8 inhibited the migration and invasion of BCa cell lines in vitro and LN metastasis in vivo. Mechanistically, circFUT8 directly bound to miR-570-3p and partially abrogated its oncogenic role, and miR-570-3p could suppress the expression of tumor suppressor gene Krüpple-like factor 10 (KLF10) by binding its 3′ untranslated region (3′ UTR). Moreover, we found that circFUT8 promoted the expression of KLF10 by competitively sponging miR-570-3p. In conclusion, circFUT8 functions as a tumor suppressor in BCa cells by targeting the miR-570-3p/KLF10 axis and may serve as a potential biomarker and therapeutic target for the management of BCa patients with LN metastasis.